Juridical Consequences of Anticipatory Breach as a Form of Breach of a Contract - Sulistianingsih, Dewi; Wijaya, Christian Chandra; Yusoff, Rahmawati Mohd; Adhi, Yuli Prasetyo (Universitas Negeri Semarang, 2024)
Default is a condition in which one of the parties does not carry out or fulfill obligations to the other party as specified in an agreement. In addition, there are several forms of default: not doing something at all, doing something but it is too late, doing something only partially, and doing something prohibited. The concept, the forms, and the consequences of default are often encountered in various literature and legal experts' opinions, unlike the concept of Anticipatory Breach, which is a form of breach of contract/default that exists universally in contract law. In Indonesia, no positive legal provisions accommodate the Anticipatory Breach concept in the form of default. Its nonexistence becomes interesting from the point of view of contract law, where sometimes the parties to the agreement directly or indirectly commit a form of anticipatory breach in implementing the agreement. So that this will raise a question how the impact of an anticipatory breach on the sustainability and implementation of the agreement that the parties have made.